A Robust feedback control design for broadband noise attenuation in a car cabin. Issue 1 (July 2017) - Loiseau, Paul; Chevrel, Philippe; Yagoubi, Mohamed; Duffal, Jean-Marc
Abstract: The application considered in this paper is the active control of broadband noise, produced by tyre/road contact, in a car cabin. The proposed control methodology aims to evaluate achievable performances depending on the frequency bandwidth in which attenuation is desired. This is explored by seeking a MIMO active noise control solution that optimizes the attenuation level, under explicit robustness constraints. Emphasis is put on how to i) formalize the related optimization problem: performance and robustness indicators, ii) perform an effective MIMO identification, and iii) fix an a priori control structure and directly optimize its parameters thanks to nonsmooth optimization solvers. Finally, the results obtained (following the proposed methodology) both in simulation and experimentally are shown and discussed.